2019
DOI: 10.1136/ijgc-2018-000036
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and oncologic outcomes after fertility-sparing management for early stage endometrioid endometrial cancer

Abstract: ObjectiveHormonal management is an alternative treatment for preserving fertility in patients with presumed early stage endometrioid endometrial cancer. This study aimed to define the pregnancy and oncologic outcomes and factors of successful conception after hormone therapy for endometrioid endometrial cancer.MethodsWe retrospectively analyzed patients presumed to have stage IA, grade 1–2 endometrioid endometrial cancer who underwent fertility-sparing treatment. Concurrent medroxyprogesterone and levonorgestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 40 publications
4
70
3
Order By: Relevance
“…Candidates should have a minimal risk of metastatic disease or local invasion and therefore a higher chance of regression; thus, the ideal candidates for fertility-sparing treatment have been suggested to be young women with grade 1 endometrioid adenocarcinoma confined to the endometrium. Few studies [4,[18][19][20] have reported the outcomes of fertility-sparing treatment for patients with more advanced disease. Park et al [18] reported the outcomes of fertility-sparing treatment for grade 2-3 EC with or without superficial myometrial invasion.…”
Section: Ideal Target Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…Candidates should have a minimal risk of metastatic disease or local invasion and therefore a higher chance of regression; thus, the ideal candidates for fertility-sparing treatment have been suggested to be young women with grade 1 endometrioid adenocarcinoma confined to the endometrium. Few studies [4,[18][19][20] have reported the outcomes of fertility-sparing treatment for patients with more advanced disease. Park et al [18] reported the outcomes of fertility-sparing treatment for grade 2-3 EC with or without superficial myometrial invasion.…”
Section: Ideal Target Patientsmentioning
confidence: 99%
“…The rates of complete response (CR) to fertility-sparing treatment were 76.5%, 73.9%, and 87.5% for patients with stage IA (without myometrial invasion) grade 2-3 disease, patients with stage IA (with superficial myometrial invasion) grade 1 disease, and patients with stage IA (with superficial myometrial invasion) grade 2-3 disease, respectively [18]. Chae et al [4] reported pregnancy outcomes of fertility-sparing treatments and demonstrated that a higher grade was also closely associated with pregnancy failure. Although a few reports have indicated that fertility-sparing treatment can be safe and effective for EC patients with grade 2-3 disease or superficial myometrial invasion [4,[18][19][20], expansion of the criteria for target patients is not yet recommended due to the paucity of high-quality evidence.…”
Section: Ideal Target Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Although less useful in assessing uterine abnormalities than MRI and US, CT scan has better multiplanar spatial resolution and is useful for visualizing large lymph nodes and pulmonary metastases in the entire abdominopelvic cavity. 11 Three retrospective series [14][15][16] have shown that follow-up with uterine curettage every 3 months is safe.…”
Section: How Should Ec Patients Be Initially Assessed In Services Witmentioning
confidence: 99%